Эволюция сигнальных систем фитогормонов растений - Жук, О.И. (Фактори експериментальної еволюції організмів, 2014)
Aims. Aim of this work was to examine the evolutionary formation of signaling systems phytohormones – auxin, cytokinins and strigolactones that have been identified in algae, microorganisms, fungi, plants. Methods. The evolution of signaling systems was conducted using mutants that allowed the identification of individual components of the signaling cascade and the interaction of plant hormones in the regulation of morphogenesis, stress response. Results. Receptor protein TIR1-AFB, AUX-IAA repressor and transcription factor ARF play key role in auxin signaling. Auxin signaling system interacts directly with the signaling network of micro RNA (mi RNA) in monitoring the functioning of the shoot apical meristem of plants, leaf primordia formation process. Auxin signal strongly correlates with the expression of the gene WUS (WUSCHEL) of subfamily WOX. Strigolactones and cytokinins also participate in the control processes of morphogenesis in plants. Strigolactones and cytokinins are characterized by the general structure of the two lactones and are derived from carotenoids. Conclusions. Investigations of recent decades have demonstrated that the interaction between cytokinin and auxin signaling is the key and the most ancient bridge in the control of plant growth and development.

Key words: signal systems, phytohormones, evolution.